Adaptation of the nutrition care process for metabolic diseases in the Mexican population - Sevilla-González, Magdalena; González-Ortiz, Ailema; Landa-Anell, María Victoria; Melgarejo-Hernández, Marco A.; Arias-Marroquín, Ana Teresa; Del Razo-Olvera, Fabiola Mabel; Román-Calleja, Berenice Monserrat; Monreal-Lugo, Ana Victoria; Martin-Vences, Angélica J.; Haua-Navarro, Karime; Espinosa-Cuevas, Angeles (Frontiers in Nutrition, 2025)
BackgroundThe Nutrition Care Process (NCP) is a systematic framework designed to enhance the quality of nutrition care. Given the high prevalence of metabolic diseases in Mexican population, there is a critical need for tailored nutrition care strategies.ObjectiveWe aim to describe the adaptation of the NCP to manage metabolic diseases in Mexican individuals.MethodsOur adaptation included a comprehensive literature review of clinical nutrition guidelines, by a structured consultation with experts to ensure clinical setting-specific and culturally appropriate modifications. A team of registered dietitians from two tier 3 hospitals, each with over five years of experience in metabolic disease management, customized the NCP’s four core steps—assessment, diagnosis, intervention, and monitoring—to meet the specific needs of the Mexican population.ResultsWe adapted the NCP to manage five common metabolic disorders: obesity, type 2 diabetes, kidney disease, metabolic dysfunction-associated steatotic liver disease, and dyslipidemia. Each step of the NCP was complemented by the development of educational materials designed to (1) enhance awareness of disease risk, (2) broaden their knowledge of nutritional management, and (3) provide tailored strategies for developing personalized action plans. The adapted NCP was implemented in clinical and research settings and the materials were documented as an online publication to facilitate widespread dissemination.ConclusionOur adaptation represents a significant advancement in the use of structured tools for nutrition care in Mexican populations, who face disproportionately high rates of metabolic diseases. Further research is needed to assess the effectiveness of this approach in clinical settings.